The Effect of Evaluation of the Implementation of the Award and Punishment System on Employee Work Productivity at PT PLN (Persero) Bintan Center Customer Service Unit - Juantommy Roichris Munthe; Dian Septiana Sari; Wulan Dayu (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the evaluation of the application of the reward and punishment system to employee work productivity. The location of the research was conducted at PT PLN (Persero) Bintan Center Customer Service Unit. This type of research is a descriptive research with a quantitative approach. The sample in this study is 105 permanent employees. The research method is multiple linear regression analysis with data calculation using the SPSS version 25 program. The results of the study show that partial awards have a positive and significant effect on employee productivity. Punishment has a positive and significant effect on employee productivity. Meanwhile, simultaneously awards and punishments have a positive and significant effect on employee productivity. The magnitude of the influence of awards and punishments (X2) on employee productivity (Y) at PT PLN ULP Bintan Center was 43.0%